A landmark-based approach to locate symptom-specific transcranial magnetic stimulation targets of depression - Du, Rongrong; Zhou, Qian; Hu, Tianzheng; Sun, Jinmei; Hua, Qiang; Wang, Yingru; Zhang, Yuanyuan; He, Kongliang; Tian, Yanghua; Ji, Gong-Jun; Wang, Kai (Frontiers in Psychology, 2022)
Objective Two subregions of the dorsolateral prefrontal cortex have been identified as effective repetitive transcranial magnetic stimulation (rTMS) targets for the “anxiosomatic” and “dysphoric” symptoms, respectively. We aimed to develop a convenient approach to locate these targets on the scalp. Materials and methods In a discovery experiment, the two personalized targets were precisely identified on 24 subjects using a neuronavigation system. Then, a localized approach was developed based on individual scalp landmarks. This “landmark-based approach” was replicated and validated in an independent cohort (N = 25). Reliability of the approach was tested by calculating the correlation of both the inter-rater and intra-rater results. Validity was tested by comparing the mean distance between the personalized and landmark-based targets to the TMS spatial resolution (i.e., 5 mm). We further conducted a total of 24 sham rTMS sessions to estimate the misplacement between the coil center and target during a 10-min stimulation without neuronavigation. Results The parameters of the “landmark-based approach” in the discovery experiment were replicated well in an independent cohort. Using discovery parameters, we successfully identified the symptom-specific targets in the independent cohort. Specifically, the mean distance between the personalized and landmark-based targets on the cortex was not significantly larger than 5 mm. However, the personalized and landmark-based targets distance exceeded 5 mm in more than 50% of subjects. During the 10-min sham rTMS session, the average coil misplacement was significantly larger than 5 mm. Conclusion The “landmark-based approach” can conveniently and reliably locate the two symptom-specific targets at group level. However, the accuracy was highly varied at individual level and further improvement is needed.